Determinants of Dietary Pattern & Non Communicable Diseases among Adult Population of Districts Kohat & Nowshera KP - Muhammad Jibran Khan, Syed Jawad Hussain, Nadia Qazi, Anwar Khan Wazir, Abdul Haq Wazir, Inayat Shah, Muhammad Ishtiaq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To estimate the burden of non-communicable diseases and to assess the dietary pattern along with important relevant determinants among adult population of district Kohat & Nowshera Khyber Pukhtunkhwa Pakistan Study Design: A descriptive cross sectional study Place & Duration: This study was conducted in Kohat & Nowshera Districts of Khyber Pukhtunkhwa Pakistan; from June to December 2022. Methodology: A total of n=385 male adults was selected and a structured questionnaire was used to collect relevant information regarding demographic, dietary, behavioral determinants. Finally data was analyzed and presented in form of text and tables. Results: Results showed that 55.71% had age above 37 years; 28.31% were illiterate; 25.71% had monthly income more than 45000/ PKR; 60.78% were married; and 82.08% were employed. Moreover, 30.39% were current tobacco smoking; and 24.68% had positive history of past tobacco smoking. Furthermore, 44.94% prefer high caloric; 40.78% vegetables; 45.19% meat; 63,38% fresh fruits; and 18.70% & 21.30% prefer too much sugar and salt in food respectively. Furthermore; hypertension, malnutrition, eye problems and cancer were found among 22.60%, 59.74%, 7.01% & 2.08% respectively. Conclusions: It was concluded that common non-communicable diseases were present in the studied male adults and showed strong relationship with dietary pattern along with demographic, epidemiological and socio-economical determinants. Moreover, effective and efficient policies and strategies were needed to reduce the double burden of non-communicable disease and its associated complications. Keywords: Prevalence, Determinants, Diet, Vegetables, Overweight, Obesity, Tobacco, Adults